1992
DOI: 10.1126/science.1546325
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic Dystrophy Mutation: an Unstable CTG Repeat in the 3′ Untranslated region of the Gene

Abstract: Myotonic dystrophy (DM) is the most common inherited neuromuscular disease in adults, with a global incidence of 1 in 8000 individuals. DM is an autosomal dominant, multisystemic disorder characterized primarily by myotonia and progressive muscle weakness. Genomic and complementary DNA probes that map to a 10-kilobase Eco RI genomic fragment from human chromosome 19q13.3 have been used to detect a variable length polymorphism in individuals with DM. Increases in the size of the allele in patients with DM are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
808
1
16

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,496 publications
(847 citation statements)
references
References 12 publications
7
808
1
16
Order By: Relevance
“…The gene is located on chromosome 19q13. 3 and was cloned in 1992 [1,2]. Expansion of an unstable CTG trinucleotide repeat is frequently observed after parent-to-child transmission in DM1 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The gene is located on chromosome 19q13. 3 and was cloned in 1992 [1,2]. Expansion of an unstable CTG trinucleotide repeat is frequently observed after parent-to-child transmission in DM1 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of CDM confirmed to correspond to the length of CTG repeats in mutant genes from peripheral blood leukocytes in our study. Mahadevan et al (1992) suggested that a blurred or smeared appearance of expanded alleles seen on Southern blots in lymphocytes indicated somatic cell heterogeneity in the size of the expanded alleles. We also observed smeared expanded bands in several DM patients on Southern blots.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was performed using CTG region-flanking primers Mahadevan et al, 1992). Cycling conditions were as follows: initial denaturation at 95°C for 3 min, 35 cycles at 95°C for 1.5 min, 65°C for l min and at 72°C for 2 min, followed by a final stage at 72°C for 7 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…602668) is caused by a (CCTG) n expansion in intron 1 of the CNBP (CCHC-type zinc-finger nucleic acid-binding protein gene, formerly ZNF9, MIM *116955) on chromosome 3q21. [4][5][6][7][8] For DM1, disease severity and age of onset show a strong correlation with the size of the repeat expansion, which is associated with the phenomenon of anticipation. 9 Variation in repeat size and in somatic repeat expansion in different tissues can partly explain the variability of the phenotype.…”
Section: Introductionmentioning
confidence: 99%